2003
DOI: 10.1097/01.aud.0000052748.94309.8a
|View full text |Cite
|
Sign up to set email alerts
|

Audibility-Index Predictions of Normal-Hearing and Hearing-Impaired Listeners’ Performance on the Connected Speech Test

Abstract: The results of this study suggest that the AI functions derived for the CST satisfactorily predict the scores of normal-hearing subjects when they listen in speech babble under audio-only conditions but not when they receive visual cues. To obtain accurate predictions for the audiovisual form of the CST, it will be necessary to develop new ANSI-style AI correction equations for visual cues or new AI functions based on audiovisual test scores. If the current AI functions are used to predict the scores of hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 32 publications
(87 reference statements)
8
36
0
Order By: Relevance
“…In this study, SII scores were computed for all participants using the online calculation procedure based on the ANSI S3. (Sherbecoe and Studebaker 2003). Thus, despite significant differences in hearing threshold levels between the participant groups, speech was audible for all participants in this study.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, SII scores were computed for all participants using the online calculation procedure based on the ANSI S3. (Sherbecoe and Studebaker 2003). Thus, despite significant differences in hearing threshold levels between the participant groups, speech was audible for all participants in this study.…”
Section: Methodsmentioning
confidence: 91%
“…Audibility was calculated using the Speech Intelligibility Index (SII). The SII, is a measure, ranging between 0.0 and 1.0 that is highly correlated with the intelligibility of speech (ANSI, S3.5, 1997), and can be used to predict speech recognition scores for specific speech materials (Sherbecoe and Studebaker 2003). In this study, SII scores were computed for all participants using the online calculation procedure based on the ANSI S3.…”
Section: Methodsmentioning
confidence: 99%
“…Most pertinent, though, is that the data indicate that for the 27 audiograms used in this study on MPT, both the Sherbecoe and Studebaker (2003) and the Ching et al (2011) desensitization factors yield near-identical reductions to the ANSI SII calculated values (within 1/100 hundredth units; Table 6). Specifically, the reduction was 0.12 using the Ching et al (2011) desensitization factor (used within NAL-NL2) and was 0.11 using the Sherbecoe and Studebaker (2003) desensitization factor. The agreement between the two datasets that lead to the derivation of these two factors is substantial evidence that at least, on average, the amount of desensitization can be accurately estimated based on measures of an audiogram.…”
Section: Is the Additional Audibility Prescribed By Dsl M[i/o] Usefulmentioning
confidence: 96%
“…The similar negative slopes imply that the reduction in expected speech intelligibility with increasing hearing loss is not impacted by the selection of prescription. (Sherbecoe & Studebaker, 2003) 0.11…”
Section: Decrement To Expected Speech Intelligibility With and Withoumentioning
confidence: 99%
“…Studies (15)(16)(17) aiming to investigate the relationship between the values of SII and speech recognition scores for different test materials with certain characteristics frequency, concluded that the frequency importance function (FIF) -required by ANSI (10) for six types of speech materials -must also be established for other types of test materials so that the speech recognition scores can be related to the values of SII. These results suggest that, in addition to the degree of hearing loss, audiometric configuration is essential to trace prognosis of audibility and intelligibility of speech.…”
Section: Introductionmentioning
confidence: 99%